2009
DOI: 10.1016/j.foodchem.2009.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supercritical carbon dioxide extraction parameters on virgin coconut oil yield and medium-chain triglyceride content

Abstract: The extraction of coconut oil has been performed using supercritical carbon dioxide (SC-CO2). The extractions were performed at pressure and temperature ranges of 20.7-34.5 MPa and 40-80 °C, respectively. It was observed that almost all (more than 99%) of the total oil could be extracted. Response surface methodology (RSM) was applied to evaluate the effects of the parameters (pressure, temperature and CO2 consumption) on the extraction yield and medium-chain triglycerides (MCTs), in terms of the fatty acid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
3
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 8 publications
2
38
3
3
Order By: Relevance
“…Linoleic acid was the predominant fatty acid in the oil from both melon seeds followed by oleic, palmitic and stearic acids with concentrations of 64, 16, 8.5 and 6%, respectively. These results were in good agreement with that of Norulaini et al, (2009) who studied the effects of supercritical carbon dioxide extraction parameters on virgin coconut oil and they reported that the composition of the fatty acid in the extracted oil varied, based on the extraction conditions. While Sanchez-Vicente et al, (2009) found no change in terms of fatty acid distribution in all the extracted peach seed oils at the conditions of acid (MUFA) and 65.92% of polyunsaturated fatty acid (PUFA).…”
Section: Fatty Acid Compositionsupporting
confidence: 90%
“…Linoleic acid was the predominant fatty acid in the oil from both melon seeds followed by oleic, palmitic and stearic acids with concentrations of 64, 16, 8.5 and 6%, respectively. These results were in good agreement with that of Norulaini et al, (2009) who studied the effects of supercritical carbon dioxide extraction parameters on virgin coconut oil and they reported that the composition of the fatty acid in the extracted oil varied, based on the extraction conditions. While Sanchez-Vicente et al, (2009) found no change in terms of fatty acid distribution in all the extracted peach seed oils at the conditions of acid (MUFA) and 65.92% of polyunsaturated fatty acid (PUFA).…”
Section: Fatty Acid Compositionsupporting
confidence: 90%
“…[75] DCM and ethyl acetate were the most popular solvents used. [85] Because of environmental issues such as ozone depletion and health risks associated with these conventional www.chemsuschem.org organic solvents, a drive for a new decaffeination method was initiated. The use of CO 2 for decaffeination was first commercialized in 1970s by cafØ HAG and General Foods in Germany, after a patent by Zosel.…”
Section: Decaffeination Of Coffeementioning
confidence: 99%
“…CO 2 is widely used as an extraction solvent for various applications. These include decaffeination of coffee and tea, [75][76] production of hops extracts for the brewing industry, [77][78] recovery of flavors and aromas from herbs and spices, [79][80] nicotine extraction from tobacco, [81][82] extraction and fractionation of edible oils, [83][84][85] and removal of contaminants as a cleaning procedure. [86][87] The effectiveness of the extraction is highly dependent on the kinetic extraction properties of the raw materials, solvent strength, and the operating conditions.…”
mentioning
confidence: 99%
“…The high cost of organic solvents, increasingly stringent environmental regulations, and new requirements of the medical and food industries for ultra-pure and high added value products have increased the need for the development of new and clean technologies for the processing of food products (Mohamed and Mansoori, 2002). Supercritical carbon dioxide (SC-CO 2 ) extraction has attracted considerable attention in recent years as a promising alternative to conventional solvent extraction and mechanical pressing for extracting oils and other materials as it offers a number of advantages, including a lack of solvent residue and better retention of aromatic compounds (Norulaini et al, 2009;Zaidul et al, 2006Zaidul et al, , 2007aHerrero et al, 2006).…”
Section: Introductionmentioning
confidence: 99%